2007
DOI: 10.1007/s10086-006-0861-9
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of mitochondrial DNA from Pleurotus ostreatus into Pleurotus pulmonarius by interspecific protoplast fusion

Abstract: Interspecific protoplast fusion between two monokaryotic strains (a methionine auxotrophic and chloramphenicol-resistant Pleurotus ostreatus strain and a wild type strain of Pleurotus pulmonarius) was carried out to introduce mitochondrial DNA (mtDNA) from P. ostreatus into P. pulmonarius. Because mycelial colonies 1 regenerated on minimum medium containing chloramphenicol only after the treatment of protoplast electrofusion, the regenerants were regarded as protoplast fusants. The fusants isolated from regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Fukuda et al (4) have reported the successful mitochondrial DNA transmission in interspecific fusion protoplasts of edible mushrooms Pleurotus ostreatu (amethionine auxotrophic and chloramphenicol-resistant strain) and Pleurotus pulmonarius (wildtype strain), thus increasing the genetic variability of economically important mushrooms. This possibility is useful in mushroom breeding, because the mitochondrial genome may affect phenotypical properties of edible mushrooms.…”
Section: Introductionmentioning
confidence: 98%
“…Fukuda et al (4) have reported the successful mitochondrial DNA transmission in interspecific fusion protoplasts of edible mushrooms Pleurotus ostreatu (amethionine auxotrophic and chloramphenicol-resistant strain) and Pleurotus pulmonarius (wildtype strain), thus increasing the genetic variability of economically important mushrooms. This possibility is useful in mushroom breeding, because the mitochondrial genome may affect phenotypical properties of edible mushrooms.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, protoplast fusion may result in interactions between nuclear and exonuclear genes, such as mitochondrial genes (Stasz and Harman, 1990;Harman and Stasz, 1991;Harman and Hayes, 1993). Fukuda has reported the successful mitochondrial DNA transmission in interspecific fusion protoplasts of Pleurotus, which increased the genetic variability of economically significant mushrooms (Fukuda et al, 2007). Because mitochondrial genomes may influence the phenotypic characteristics of edible mushrooms, this possibility is useful in mushroom breeding (Zhao and Chang, 1997).…”
Section: Discussionmentioning
confidence: 99%